Maintaining Valencia orange quality during shelf life using different waxes - Khedr , Emad H (Journal of Postharvest Technology, 2018)
Extending postharvest fruit life demand elongation cold storage period with reasonable shelf life, in this scope quality of Valencia orange was determined in response for Arabic gum, bee wax, paraffin oil and chitosan coatings during simulated shelf life at 20°C for 12 days after cold storage at 5°C and 90-95% relative humidity for 90 days. All applied coatings had desirable effects on fruit quality, chitosan at 2 and 1% were effective in maintaining ascorbic acid content compared to uncoated ones. Chitosan coating at 2% attained the lowest significant weight loss and decay percentages, also it delayed changes associated with fruit aging such as colour changes, softening and pectin methylesterase activity. In addition to valuable means of respiration rate compared to uncoated ones.